Aromatase Derived Estradiol Within the Thalamus Modulates Pain Induced by Varicella Zoster Virus - Kramer, Phillip R.; Rao, Mahesh; Stinson, Crystal; Bellinger, Larry L.; Kinchington, Paul R.; Yee, Michael B. (Frontiers in Integrative Neuroscience, 2018)
HAbstract Herpes zoster or shingles is the result of varicella zoster virus (VZV) infection and often results in chronic pain that lasts for months after visible symptoms subside. Testosterone often attenuates pain in males. Previous work demonstrates ovarian estrogen effects GABA signaling in the thalamus, reducing pain but the role of testosterone within the thalamus is currently unknown. Because aromatase affects pain and is present in the thalamus we tested a hypothesis that testosterone converted to estrogen in the thalamus attenuates herpes zoster induced pain. To address this hypothesis, male Sprague-Dawley rats received whisker pad injection of either MeWo cells or MeWo cells containing VZV. To reduce aromatase derived estrogen in these animals we injected aromatase inhibitor letrozole systemically or infused it into the thalamus. To test if estrogen was working through the estrogen receptor agonist, 4,4',4''-(4-Propyl-[1H]-pyrazole-1,3,5-triyl)trisphenol (PPT) was infused concomitant with letrozole. Motivational and affective pain was measured after letrozole and/or PPT treatment. Vesicular GABA transporter (VGAT) is important in pain signaling. Because estrogen effects VGAT expression we measured its transcript and protein levels after letrozole treatment. Virus injection and letrozole significantly increased the pain response but thalamic infusion of PPT reduced zoster pain. Letrozole increased the number of thalamic neurons staining for pERK but decreased VGAT expression. The results suggest aromatase derived estradiol interacts with the estrogen receptor to increase VGAT expression and increase neuronal inhibition in the thalamus to attenuate VZV induced pain.